Cambridge academic English - Hewings, Martin (Cambridge University Press, 2012)
A three-level (B1+ to C1) integrated skills course for higher education students at university or on foundation courses. Designed specifically for students preparing for university, this integrated skills course develops language and real academic skills essential for successful university studies across disciplines. With authentic lectures and seminars, language informed by the Cambridge Academic Corpus and Academic Word Lists, the course guarantees the English that students learn is up to date and relevant to them. The Teacher's Book provides extensive teacher support including teaching notes and additional photocopiable worksheets for the classroom